Leflunomide Induced Toxic Epidermolysis Necrosis in Patient with Rheumatoid Arthritis - Pyakurel, Bibek; Basnet, Prava (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Leflunomide is immunomodulating agent used in rheumatoid arthritis and other rheumatic diseases like psoriatic arthritis and systemic lupus erythematous. Minor side effects of leflunomide (<10%) are rash, purpura but only severe case can lead to Steven johnson syndrome( SJS) or toxic epidermolysis. Causative agent (leflunomide) was discontinued and TEN was treated with methylprednisolone, cholestyramine and immunoglobulin. The skin lesion eventually resolved within 2-3 weeks with some hyperpigmentation. Leflunomide is a drug that was used to prevent transplant rejection, however it’s use has been diversified in treating in rheumatic diseases, psoriatic arthritis and SLE. Rheumatic diseases is autoimmune diseases that affects joints, tendon, muscle, ligaments, bones and muscles. We present the case of patient with rheumatic arthritis, who had been receiving leflunomide, prescribed by rheumatologist. The patient attends our hospital with picture of TEN after started using leflunomide